Comparative toxicokinetics of Fusarium mycotoxins in pigs and humans. (March 2020) - Schelstraete, Wim; Devreese, Mathias; Croubels, Siska
Abstract: Mycotoxins frequently contaminate food and feed materials, posing a threat to human and animal health. Fusarium species produce important mycotoxins with regard to their occurrence and toxicity, especially deoxynivalenol (DON), fumonisin B1 (FB1), zearalenone (ZEN) and T-2 toxin (T-2). The susceptibility of an animal species towards the effects of these toxins in part depends on the absorption, distribution, metabolism and excretion (ADME processes) of these toxins from the body. For humans, in vivo information is scarce and often animal data is used for extrapolation to humans. From a kinetic and safety point of view, the pig seems to be a promising animal model to aid in the assessment of the toxicological risk of mycotoxins to humans. Qualitatively, the ADME processes seem to be quite similar between pigs and humans. In addition, similar metabolite and excretion patterns are observed, although some quantitative differences are noticed which are subject of this review. The high sensitivity of pigs towards mycotoxins and the similar kinetics are an advantage for the use of this animal species in the risk assessment of mycotoxins, and for the establishment of legal limits of mycotoxins. Highlights: Concerning toxicokinetics, the pig is a promising model in the assessment of the toxicological risk of mycotoxins to humans. Qualitatively, the ADME processes seem to be quite similar between pigs and humans. Similar metabolite and excretion patterns are observed, although some quantitative differences are noticed.